Does direct admission from an emergency department with on-site neurosurgical services facilitate time critical surgical intervention following a traumatic brain injury in children?. (June 2013) - Fayeye, O.; Ushewokunze, S.; Stickley, J.; Reynolds, F.; Solanki, G.; Rodrigues, D.; Walsh, A. R.; Kay, A.
Abstract Objectives. To compare the proportion of trauma craniotomies performed within 4 hours of presentation to emergency departments (ED) with and without on-site neurosurgery. Design. A retrospective cohort analysis of data collected prospectively between January 2005 and April 2010 from patients with traumatic brain injury who were admitted to the paediatric intensive care unit (PICU) following traumatic brain injury. Methods. Times for admission to ED, PICU and theatre were obtained through analysis of prospectively collected data management systems. Emergency department admission to neurosurgical theatre lag time was calculated using Microsoft Excel. Statistical analysis was performed using R (version 2.11.0). Subjects. Fifty-seven cases were identified. Twenty patients were admitted directly from ED to an on-site neurosurgical unit. The remaining 37 were transferred from regional EDs. Results. Thirty-one craniotomies were performed. Thirteen in-patients admitted directly to hospital with neurosurgery on site. Eighteen in patients admitted at the local hospital and then transferred to the neurosurgical unit. Thirteen of Thirty-one (42%) craniotomies were performed within 4 hours. In the on-site group 10 of 13 (77%) craniotomies were performed within 4 hours compared to 3 of 18 (17%) in those transferred from regional ED (p = 0.001232) (Fisher exact test). Eleven patients were transferred directly from ED to neurosurgical theatre for emergency craniotomies. Within this subgroup, seven patients came from the cohort of admissions to a hospital with on-site neurosurgery. The remaining four patients were transferred from regional ED. There were eight extradural haematomas, one subdural haematoma and two intraparenchymal haemorrhages. The mean time from ED presentation to theatre was 1.68 hours and 5.46 hours for the on-site and regional transfer groups, respectively. There were no mortalities. Conclusions. Forty-two per cent of trauma craniotomies are performed within 4 hours. However, presentation to an ED with on-site neurosurgical services significantly facilitates time critical surgery in children following a traumatic brain injury.